Campaña de comunicación integral para la Asociación Peruana de Agencias de Viajes y Turismo (APAVIT) - Goicochea Escate, Steffi (2020)
The purpose of this project is to develop a communication campaign so that the Peruvian traveling public of socioeconomic levels A, B and C can recognize the Peruvian Association of Travel and Tourism Agencies (APAVIT), as the association that disseminates and preserves the tourism of our country through the drive of travel with its partners, travel agencies.